Data from: Study "Red fox Bylot - Argos tracking" ... - Berteaux, Dominique (Movebank Data Repository, 2021)
Rapid range expansion of boreal forest predators onto the tundra may disrupt local ecological processes, notably through competition with ecologically similar species. Red foxes (Vulpes vulpes) have expanded their range northwards throughout the Canadian Arctic, inducing competition with endemic Arctic foxes (V. lagopus). We studied competition between Arctic and red foxes, with a focus on interference competition, and winter movements of red foxes using satellite telemetry and den occupancy data from both species. We worked at Bylot Island (Nunavut) and Herschel Island (northern Yukon), two sites at the northern limit of the red fox’s range. As expected, red fox home ranges were 56% larger on average than Arctic fox home ranges. However, red foxes did not exclude arctic foxes regionally nor did they prevent them from breeding successfully in their vicinity. On Bylot Island, Arctic foxes did not spatially avoid red foxes more than their conspecifics, as evidenced by similar intra- and inter-specific ...